Struktur ekosistem lamun di Desa Teluk Bakau, pesisir bintan timur-Indonesia - Aditya Hikmat Nugraha; Endang S Srimariana; Indra Jaya; Mujizat Kawaroe (Depik, 2019)
Abstract. Teluk Bakau Village is one of the largest conservation areas of seagrass ecosystem located in Bintan Island. This research aim to study the distribution of species, seagrass coverage and seagrass density in Teluk Bakau Village. The research was conducted at two stations, Beralas Pasir Island and Teluk Bakau Village Beach. Seagrass data collections are computed using transect quadrat method. The results of this study show that there is total 8 species of seagrasses found in the conservation area of seagrass ecosystem in Teluk Bakau, namelu Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serulata, Halophila ovalis, Halophila minor, Syringodium isoetifolium and Halodule uninervis. The highest seagrass cover value was found at Beralas Pasir Island station about 47%, while in Teluk Bakau Village Beach station the seagrass coverage value was arround 29%. Based on these coverage value, the seagrass ecosystem in Teluk Bakau area fall in the category of medium conditon. The excistence of seagrass ecosystem in Teluk Bakau village is utilized by the community in small scale fisheries activity, therefore it is utmost important that its biodiversity and level of coverage are maintaned or even improved.Keywords: Bintan, conservation, coverage, seagrass, teluk bakauAbstrak. Desa Teluk Bakau merupakan salah satu kawasan konservasi ekosistem padang lamun yang terletak di Pulau Bintan. Penelitian ini bertujuan untuk mengkaji sebaran spesies, tutupan dan kerapatan lamun di Desa Teluk Bakau. Metode pengamatan ekosistem padang lamun dengan menggunakan metode transek kuadrat. Penelitian dilakukan di dua stasiun yaitu Pantai Timur Teluk Bakau dan Pulau Beralas Pasir. Hasil dari penelitian ini menunjukan bahwa total terdapat 8 spesies lamun yang ditemukan di kawasan konservasi ekosistem padang lamun di Teluk Bakau, meliputi spesies Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serulata, Halophila ovalis, Halophila minor, Syringodium isoetifolium dan Halodule uninervis. Nilai tutupan lamun tertinggi ditemukan di stasiun Pulau Beralas Pasir sebesar 47% dan stasiun Pantai Desa Teluk Bakau memiliki nilai tutupan lamun sebesar 29%. Berdasarkan nilai tutupannya ekosistem padang lamun di kawasan Teluk Bakau berada dalam kondisi sedang. Keberadaan ekosistem lamun di Desa Teluk Bakau dimanfaatkan oleh masyarakat dalam aktivitas perikanan skala kecil, sehingga sangat penting untuk menjaga keberagaman dan nilai tutupan ekosistem lamun.Kata Kunci: Bintan, konservasi, lamun, Teluk Bakau, tutupan